A FORMAÇÃO DO PROFESSOR DE LÍNGUAS FRENTE À PRÁTICA DE INCLUSÃO OU EXCLUSÃO - Moura, Lígia Cirana Rocha de (2013)
The object of this research is to discuss the Brazilian policy of the inclusion and actual application of the Spanish Language in regular schools for students with special educational needs and considers the non-use of special classrooms. It points out to all students with or without special educational needs the benefits of living with diversity, respecting differences, or as stimuli to their development. It questions what students without special educational needs are actually learning. It discusses what intellectuals have to say regarding the inclusion in schools of students with special educational needs in relation to educational literature aimed at the teaching and learning of languages. It reflects upon the qualification and capabilities of the Spanish teacher relating to the inclusion of the students with special educational needs, taking investigative action in line with public policies on teacher training as well as the National Curriculum Guidelines for undergraduate education.